Problems of Dostoevsky's Poetics - Bakhtin, M. M. (Mikhail Mikhaĭlovich), 1895-1975 (Book collections on Project MUSE., 1984)
This book is the ideal introduction to the thought of Mikhail Bakhtin. Bakhtin is becoming established as one of the giants of 20th century literary criticsm, despite his work being unknown in the West until the 1970's. This book is less about Dostoyevsky per se, rather a profound meditation on how Dostoyevsky's art exemplifies the central concern of Bakhtin, the concept of 'dialogism'. This idea defies a simple definition; the book in exploring manifold aspects of it, itself becomes truly dialogic. If you value Dostoyevsky as an artist, require an antidote to the chill winds of modern 'Theory', or simply appreciate genius at work, catch up with one of the best kept secrets in literature.